Rancang Bangun Sistem Informasi Pemesanan Spare Part Alat Kontraktor Pada PT. Ichtiar Teknik Utama Balikpapan - I Gusti Ngurah Thierry Agusta; M.J Dewiyani Sunarto; Endra Rahmawati (Jurnal Sistem Informasi Universitas Dinamika, 2018)
PT. Ichtiar Teknik Utama is a company engaged in manufacturing services and spare part supplier contractor tools, lathe, electric welding shop. To conduct its business processes PT. Ichtiar Teknik Utama serve ordering Spare part of contractor equipment based on consumer demand. The ordering system that runs on the company is too many involve the consumers which causes the ordering process complicated and difficult for consumers. In addition, There Lots of using hardcopy as media storage. It’s cause the Listing of ordering in the ledger is not good and will be difficult in making ordering report. Other than that, some of the data obtained can be lost, tucked, and also difficult to read. It takes a long time and complicates the preparation of reports. To improve efficiency and ordering listing process better, so it will need Ordering Information Systems of Spare Parts Contractor Equipment. The Information System has many processes including Registration, Ordering, Listing of Goods Orders, design, calculation of the price of goods, Approval, Payment and invoicing also reporting which used for decision making by the director of workshop. By implementing this information system, each section can perform the work more easily and be better when recording the order.Keywords: Information Systems, Ordering spare part, Contractor Equipment.